PENGARUH PEMBERIAN KOMPOS KULIT BUAHKAKAO TERHADAP PERTUMBUHAN BIBIT KAKAO HIBRIDA (Theobroma cacao L.) - Doni Saragih1 Pasdo Saragih; Ardian Ardian (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This study aims to determine the influence and best treatment of cocoa fruit skin compost on the growth of hybrid cocoa seeds. This research was conducted in Experimental Garden of Agriculture Faculty of Universitas Riau, Bina Widya Campus, Simpang Baru Village, Tampan Sub District, Pekanbaru. This research was conducted for 4 months starting from April to August 2016. The experiment was conducted experimentally using Completely Randomized Design (RAL) consisting of 6 treatments: K0 (without compost), K1 (12.5 g), K2 (25 g), K3 (37.5 g), K4 (50 g), and K5 (62.5 g) cocoa peel compost per polybag and repeated 3 times, to obtain 18 units of experiment. Each unit of experiment consists of 2 plants and at the same time made the sample so that there are 36 plants. Parameters observed were number of leaves, plant height, leaf area, stem circumference, and root canopy ratio. The data obtained were analyzed statistically using Analysis of Variance (ANOVA) and continued with Duncans New Multiple Range Test (DNMRT) at 5% level. The results showed that the giving of cocoa leaf compost gave a real effect on the growth of plant height, leaf area, and stem circumference. Provision of 12.5 g / polybag cocoa leaf compost is the best treatment on plant height parameters, leaf area, and stem circumference. Keywords :Theobroma cacao L, compost, nursery.